Knowledge Regarding Reproductive Health and its Relationship to Sexual Behavior in Adolescents - Kasyafiya Jayanti; Pujiati; Damayanti, Rini; Ambariani (Jurnal MIDPRO, 2024)
Teenagers tend to face various challenges, both social and health problems. One problem is sexual activity when they lack adequate knowledge and skills for self-protection. This puts teens at higher risk for health problems. This study aims to examine the relationship between knowledge about reproductive health and sexual behavior in adolescents. This type of research is quantitative with a cross sectional design. The sample was taken using a total sampling technique, namely 35 teenagers from class IX. The independent variable in the research is teenagers' knowledge about reproductive health and the dependent variable is teenagers' sexual behavior. Data was taken directly using a questionnaire instrument. The instrument was created by the researcher himself based on a literature review and other instruments used in similar research. Before the instrument is used, validity and reliability tests are carried out first. The results of the bivariate analysis of the relationship between adolescent knowledge about reproductive health and sexual behavior were 80% had good knowledge and positive behavior. Teenagers who have less knowledge but still behave positively are 36.4%. Teenagers who have sufficient knowledge and behave positively are 100% and none have negative behavior at all. Teenagers who have poor knowledge and behave negatively are 63.6% and as many as 20.0% of teenagers have good knowledge but still behave negatively. The results of statistical analysis of the chi square test showed a p value of 0.005 (p<0.05) which shows that there is a relationship between adolescent knowledge about reproductive health in class IX students. Adolescent sexual behavior is influenced by several factors, one of which is knowledge. One of the factors of negative sexual behavior is a lack of correct information about sexuality. Good knowledge will influence reproductive health behavior and increasing knowledge is very important to prevent negative reproductive health behavior. Cooperation is needed from parents, schools and related health services in improving quality reproductive health services for adolescents.